1999
DOI: 10.1006/jsbi.1999.4194
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Cellulose Microfibril Angles in Softwoods and Hardwoods—A Possible Strategy of Mechanical Optimization

Abstract: Position-resolved small-angle X-ray scattering was used to investigate the nanostructure of the wood cell wall in two softwood species (Norwegian spruce and Scots pine) and two hardwood species (pedunculate oak and copper beech). The tilt angle of the cellulose fibrils in the wood cell wall versus the longitudinal cell axis (microfibril angle) was systematically studied over a wide range of annual rings in each tree. The measured angles were correlated with the distance from the pith and the results were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
131
2
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(147 citation statements)
references
References 13 publications
12
131
2
2
Order By: Relevance
“…Only the first tissue slice showed a slightly higher MFA. However, these findings were contrary to other observations indicating different MFAs in earlywood and latewood Lichtenegger et al 1999). Lichtenegger et al (2003) have shown that MFAs which are measured by cross-field pitting are likely to be overestimated in earlywood.…”
Section: Discussioncontrasting
confidence: 93%
“…Only the first tissue slice showed a slightly higher MFA. However, these findings were contrary to other observations indicating different MFAs in earlywood and latewood Lichtenegger et al 1999). Lichtenegger et al (2003) have shown that MFAs which are measured by cross-field pitting are likely to be overestimated in earlywood.…”
Section: Discussioncontrasting
confidence: 93%
“…However, the obtained MFA values correspond to the values reported by other authors (e.g. Lichtenegger et al, 1999;Gierlinger et al, 2010), who proved that the MFA in the spruce wood, especially in rings placed further from the pith, may be close to 0°. Bearing in mind that the correlations between MFA and modulus of elasticity and tensile strength are negative (Fig.…”
Section: Standard Deviation Standardna Devijacijasupporting
confidence: 89%
“…3b) even if it is less significant in comparison to the findings in loblolly and radiata pine [4,29]. However, the observed MfA values, with a mean of 11 • and a variation from 8 • to 20 • , indicates that the majority of wood measured has reached maturity in respect to MfA [26,41,42]. The boards were extracted between ring 4 and cambium, which varied to be 13-21 rings from pith.…”
Section: Correlationsmentioning
confidence: 92%